2019
DOI: 10.1155/2019/6048954
|View full text |Cite
|
Sign up to set email alerts
|

An Overall Glance of Evidence Supportive of One-Hour and Two-Hour Postload Plasma Glucose Levels as Predictors of Long-Term Cardiovascular Events

Abstract: This review summarizes the vast literature describing the long-term epidemiological studies with emphasis on postprandial glucose as a stronger predictor of cardiovascular complications as compared to fasting glucose and HbA1c. Many molecular studies also supported this fact by illustrating that postchallenge hyperglycemia is associated with elevated biomarkers of systemic inflammation in the plasma and thus increasing the chances of vascular damage. Large-scale studies have proved that vascular stiffness, bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…[ 38 , 39 ] Therefore, both 1hPG and 2hPG are important in predicting long-term cardiovascular disease. [ 40 ] Third, 2hPG was based on OGTT, and our results cannot, therefore, be applied to postprandial glucose. A postmeal hyperglycemic episode after breakfast was reported not to be predictive of cardiovascular events in patients with established CAD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 , 39 ] Therefore, both 1hPG and 2hPG are important in predicting long-term cardiovascular disease. [ 40 ] Third, 2hPG was based on OGTT, and our results cannot, therefore, be applied to postprandial glucose. A postmeal hyperglycemic episode after breakfast was reported not to be predictive of cardiovascular events in patients with established CAD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of the literature has concluded that the postprandial glucose values are the main predictors of future CVD incidence, even in those without type 2 diabetes [ 4–6 , 20 ].Our study confirms the previous findings and highlights the significance of 1-h PG as the strongest determinant of CVD events and mortality. Such predictive capacity of 1-h PG was previously supported by the Malmö Preventive Project.…”
Section: Discussionmentioning
confidence: 99%
“…A higher protein diet confers its benefits in several ways: (1) dietary protein has the highest thermic effect of feeding among the macronutrients, which improves energy balance for weight control purposes (Calcagno et al, 2019 ); (2) a meal higher in protein with concomitantly reduced carbohydrate content elicits lower postprandial glucose responses (Gannon & Nuttall, 2004 ; Nuttall & Gannon, 1991 ). Postprandial glucose response is not only the main determinant of the overall glucose control (i.e., hemoglobin A1c), but also an independent risk factor for the development of cardiovascular diseases (Mann et al, 2019 ; Monnier & Colette, 2006 ); and (3) a meal with higher protein and reduced carbohydrate content can improve blood lipid profiles by limiting substrate availability (i.e., carbohydrate) for de novo lipogenesis in the liver (Sanders & Griffin, 2016 ). Thus, an LC/HP diet may counteract some of the maladaptive physiological changes with SCI.…”
Section: Introductionmentioning
confidence: 99%